Forecasting Rice Paddy Production in Aceh Using ARIMA and Exponential Smoothing Models - Nurviana, Nurviana; Amelia, Amelia; Riezky Purnama Sari, Riezky Purnama Sari; Ulya Nabilla, Ulya Nabilla; Talib, Taufan (CAUCHY, 2022)
Indonesia targets Aceh to be one of the paddy production centers and be able to carry out self-sufficient production in paddy and become a national granary. However, in reality, Aceh's paddy production in its province is not consistent from year to year. This province has not been able to meet the food needs of paddy independently, so that it supplies paddy from other regions due to the difficulty of detecting the presence of a surplus of paddy. The purpose of this research is to estimate the results of paddy production in Aceh for the future. The mathematical model that can be used is a time series model namely Autoregressive Integrated Moving Average (ARIMA) and Exponential Smoothing. The results of the estimation ofÂ  paddy production in the next 5 years using the ARIMA (1,1,3) model are 2000616; 2017549; 1903585; 1944499; and 1929810. While the estimation results using the Winter Exponential Smoothing model are 1625925; 1645196; 1687667; 1605530; and 1555213. ARIMA model (1,1,3) produces an MSE/MAD value of , while the Winter Exponential Smoothing model produces an MSE/MAD value of . Therefore, it can be concluded that the Winter Exponential Smoothing model.